PENERAPAN MOBILE TECHNOLOGY ACCEPTANCE MODEL (MTAM) DALAM MENGGUNAKAN QRIS SEBAGAI SISTEM PEMBAYARAN DIGITAL DI JAWA TIMUR - Farah Wulandari Pangestuty; Laila Hikmatul Khoiroh (Contemporary Studies in Economic, Finance and Banking, 2022)
Among various payment systems available today, QRIS is interesting to be studied due to its recentness, distinctive features, and rapid development. The objective of this research is to identify public perceptions concerning QRIS services viewed from the effects of Mobile Usefulness (MU), Mobile Ease to Use (MEoU), Mobile Perceived Trust (MPT) on Behavioral Intention (BI). This quantitative research uses multiple linear regression in analyzing data that was acquired through questionnaires. This study finds that Mobile Usefulness (MU), Mobile Ease to Use (MEoU), Mobile Perceived Trust (MPT) positively and significantly influence Behavioral Intention (BI). This happens because people feel that QRIS is beneficial, simple, and trustworthy in helping them making transactions. The findings support the result of previous researches that, when a person has decided to use a service continuously, he had considered the aspects of benefit, simplicity, and trustworthiness from cellular service providers. The provider of QRIS service is expected to improve usefulness, simplicity, and security because the public concern much about those three aspects in using cellular services. Next researches are suggested not to use the variables above, i.e. Mobile Usefulness (MU), Mobile Ease of Use (MEoU), Mobile Perceived Trust (MPT), because several studies have explained that the said variables have constant linkage with behavioral intention.